Recovery patterns and a linguistic therapy model of Sundanese-Indonesian bilingual aphasia: A neurolinguistic study - Nasrullah, Riki; Suganda, Dadang; Wagiati, W.; Riyanto, Sugeng (Universitas Pendidikan Indonesia, 2019)
This study observed a 54-year-old patient with Sundanese-Indonesian bilingual aphasia at one brain hospital in Jakarta, Indonesia. He underwent a speech therapy with the treatment given to his second language (Indonesian) during the first 2 weeks of post-onset, and received treatment to his both languages simultaneously for one and a half months post-onset. This research was conducted by using two approaches, namely, a theoretical approach and a methodological approach. In terms of the theory, the approach used in this study is neurolinguistic. In terms of the methodology, the approach is analytic-descriptive with a cohort method. The patient had been diagnosed with having expressive-receptive aphasia in both languages. Three-time evaluations of his competence in his two languages (during the period of one and a half months post-onset) showed an interesting recovery pattern. In the first evaluation result (two weeks post-onset), it was found that the patient showed a nonparallel recovery; Indonesian (the second language) recovered earlier than Sundanese (the first language). However, in the second evaluation result (a month post-onset), it was found that the improvement in proficiency of the languages showed a parallel recovery; the proficiency improvement of Indonesian after having been given treatment in the therapy showed a recovery parallel to that of Sundanese, even though Sundanese had not been given any treatment at all for a month post-onset. The linguistic track record of this patient showed that Indonesian had a higher level of familiarity compared to Sundanese, and this is correlated with the recovery process of both the languages.